Weed Management in Blackberry - Peter J. Dittmar; Jeffrey G. Williamson (EDIS)
This fact sheet is part of the Weed Management Guide that been updated with new recommendations. Written by Peter J. Dittmar and Jeffrey G. Williamson, and published December 2011. Reviewed October 2014.